Reading in Silence: Translations of Homosexual-Themed Fiction in State-Socialist Hungary and Estado Novo Portugal - Gombár, Zsófia (TTR, 2022)
The present study examines the Portuguese right-wing and Hungarian communist regimes’ attitudes towards homosexuality and sexual minorities through an analysis of English-language literary works translated and published in Hungary and Portugal between 1939 and 1974. One of its main objectives is to contribute to the scarce body of research on the history of non-normative sexualities by mapping literary works in English that might have been read by the queer community as possible self-help literature in the two countries. Besides the prevailing publishing practices, the modi operandi of the Hungarian and Portuguese censoring apparatuses are compared to see what kind of translated literature with homosexual content was or was not allowed to be published under the two opposing dictatorial regimes and why. The research draws heavily on the book censorship files stored at the National Archives of the Torre do Tombo in Lisbon along with the findings of the Hungarian project English-Language Literature and Censorship (1945-1989) and the project Intercultural Literature in Portugal 1930-2000: A Critical Bibliography.